The relationship between population of rhincoeros beetle (Oryctes rhinoceros) and the nutrient content (N,P,K) in the oil palm / Nurulzarifa Ahmad Zaini - Ahmad Zaini, Nurulzarifa (Faculty of Plantation and Agrotechnology, 2018)
The purpose of this study is to conduct an inquiry of rhinoceros beetle outbreak in oil palm due to the nutrient content on the leaf and how nutrient content in the oil palm related to the pest attack. The objective of the study is to identify the relationship between leaves nutrient content and the presence of Rhinoceros Beetle (RB) in oil palm. Completely Randomized Design (CRD) experimental design was implemented during collecting the samples. Tangkak, Johor were chosen to collect the data by setting up the pheromone trap in eight places. Thus, for nutrient analysis, four samples of leaves were undergo the process of dry ashing method to obtain the nutrient of potassium (K) and phosphorus (P) and analyse it in the ICP machine to determine the nutrient. For the nutrient nitrogen the samples were send to Carbon nitrogen sulphur analyzer. The data retrieved from conducted experiment was analysed by using IBM SPSS software on the correlation calculation method. It was found that the nutrient level in the leaves does give influence to the population of rhinoceros beetle in the selected area. The results showed that there is significant difference (P-value=0.000<0.05) between nitrogen, phosphorus and potassium with rhinoceros beetle.